Analisis Literasi Keuangan dan Hambatan Adopsi Digitalisasi pada UMKM Sektor Kuliner : Studi Kasus Warung Makan Selera Asal - Saputri, Ayu Mulya; Maharani, Edwi Fanesia; Rahajuni, Dijan; Anggraeni, Oki (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Financiall literacy and digital transformation have emerged as two critical pillars in driving the growth and sustainability of Micro, Small, and Medium Enterprises (MSMEs), especially within the culinary sector. The rapid expansion of digital technology presents substantial opportunities for business owners to broaden their market rearch, streamline operational processes, and facilitate more accessible transactions. Nevertheless, the rate of digital adoption among MSMEs continues to lag behind expectations. This study seeks to examine the extent to which financial literacy influences the barriers encountered by MSMEs in adopting digital technology, drawing on case study of Warung Makan Selera Asal in Purwokerto. A descriptive qualitative approach was employed, with data gathered through in-depth interviews, direct field observation, and documentation, further indicate that while the business owner demonstrates a foundational understanding of financial management, the practical application of this knowledge remains constrained, as evidenced by reliance on manual bookkeeping and the absence of a clear boundary between personal and business finances. Furthermore, digital adoption has yet to reach an optimal level, hindered by factors including insufficient human resource capacity, skepticim toward the reability of digital systems, and the perceived burden of costs assosiated with digital platforms. These findings suggest that financial literacy contributes to shaping MSMEs’ readiness for digital adoption, yet does not function as the sole determinant. According, a well-rounded strategy encompassing capacity building initiatives and sustained external support is essential to accelerate digital adoption and strengthen overall MSMEs performance.